Improving the Loyalty of Online Transport User Trough Brand Image, Brand Awareness, and Brand Trust - Nani Fitriani; Tiara Paramita (MEC-J (Management and Economics Journal), 2022)
This study aims to analyze the influence of brand image, brand awareness and brand trust on loyalty of grab bike users. Maintaining customer loyalty become the focus of this study since it is a crucial aspect of any company, including online transportation company to survive in a tight competition. This research is a quantitative study, using a sample of 75 grab bike users as respondents, who represent grab bike users in the area of Jakarta, Bogor, Depok, and Bekasi as the population of this study. The data collected from the questionnaires distributed via google form were analyzed using SPSS. The results of the study indicate that brand image does not have a significant influence on loyalty of grab bike users. Moreover, brand awareness does not influence the loyalty of grab bike users as well. Furthermore, brand trust partially does not have a positive and significant influence on the loyalty of grab users. On the other hand, brand image, brand awareness and brand trust simultaneously have a positive influence on the loyalty of grab bike users. With the limitation of research area, future research may develop a wider sample of grab bike users in different area or in a wider area.